Effect of information gap activities on speaking performance of extrovert and introvert EFL female students in Rumah, Saudi Arabia - Almziad, Amal Abdullah M (2021)
Communicative activities have played a significant role in second language teaching and learning. However, using information gap effectively remains to be one of the key challenges of such activities to encourage a meaningful information exchange between learners. Moreover, personality type affects the way people respond to stimuli and their preference for learning. The study aims to investigate the effect of information gap activity (IGA) on the speaking performance of extrovert and introvert EFL female students in Rumah, Saudi Arabia. Specifically, this study investigates the effect of implementing communicative activities (information gaps) on extrovert and introvert learners, as well as the reactions and perceptions of students towards these activities. This research employed a mixed-methods design using an embedded experimental model with a quasi-experimental non-equivalent control group. Seventy-five students at a second intermediate school in Saudi Arabia were selected purposively for experimental and control groups. Eysenck Personality Questionnaire was used to identify extrovert and introvert students in both groups. Then, twenty information gap sessions were carried out and data were collected using three quantitative and qualitative instruments: English language speaking pre- and post-tests, classroom observations, and focus group discussions (FGD). The result of the effect of IGA on the experimental group was 3.07, while the effect of IGA on the control group was 1.23. In addition, the results of the independent samples t-test for the experimental group for fluency, grammar, pronunciation, vocabulary, interaction, and content of speaking performance after treatment were significant with p values less than 0.05, which indicated that the students’ speaking performance improved after implementing IGA in the classroom. Meanwhile, the results from ANOVA indicated that there was a statistical difference between the extroverted and introverted students in the experimental group with a significant value of p=0.00. These results reflected the findings from the classroom observations, which showed positive responses from the extrovert and introvert students towards IGA when engaging in pair and group work activities. Furthermore, the qualitative findings supported the quantitative results of the study as the data from the FGD also revealed ii extrovert and introvert students’ positive reactions towards the IGA implementation in the classroom. The students in the focus group specifically explained how they enjoyed the activities designed for pair work. They reported that these activities provided them opportunities to practice and develop their English. Hence, this research established the positive effect of communicative activities in learning a second language for extrovert and introvert students, particularly in terms of developing speaking skills. This research suggests that Saudi English educators should implement communicative activities and information gap activities. Finally, when new teaching methods or approaches suggested by this study are implemented in the classroom, educators should consider students’ perceptions towards the method, as well as its effect on learning outcomes and personality as a part of the whole learning and teaching process.